Celine : a novel - Heller, Peter, 1959- (Alfred A. Knopf, 2017)
"From the best-selling author of The Dog Stars and The Painter, a luminous, spine-tingling novel of suspense--the story of Celine, an elegant, aristocratic private eye who specializes in reuniting families, trying to make amends for a loss in her own past"--